Spatial Analysis of Air Pollution in selected Central European countries - Egwuchukwu, Melody Ogechi; Formánek, Tomáš; Lacko, Jindřich; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis investigates the spatial analysis of air pollutants (Carbon Monoxide (CO), Ozone (O3), and Nitrogen Dioxide (NO2)) across selected Central European countries, focusing on their correlation with population density. Utilizing spatial analysis techniques and statistical analyses, the study examines the geographic distribution, spatial patterns, and relationships between air pollutant concentrations and population size.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses